2021
DOI: 10.3389/fmicb.2021.604555
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genomic Variability of Serial Peri-Lung Transplantation Pseudomonas aeruginosa Isolates From Cystic Fibrosis Patients

Abstract: Cystic fibrosis (CF) represents one of the major genetic and chronic lung diseases affecting Caucasians of European descent. Patients with CF suffer from recurring infections that lead to further damage of the lungs. Pulmonary infection due to Pseudomonas aeruginosa is most prevalent, further increasing CF-related mortality. The present study describes the phenotypic and genotypic variations among 36 P. aeruginosa isolates obtained serially from a non-CF and five CF patients before, during and after lung trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…However, the genetic mediators of persister formation for P. aeruginosa are poorly understood [ 4 ]. In the current study, genome sequencing of persister-forming isolates revealed that they had smaller genomes (4.66–4.9 Mbp), compared to PAO1-genome (6.3 Mbp) sequenced previously [ 55 ], and the genome of Pseudomonas CF-isolates (6.36 Mbp) recently sequenced [ 50 ]. The smaller genome size for our isolates could be due to the short-reads-based sequencing and assembly used in our study.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…However, the genetic mediators of persister formation for P. aeruginosa are poorly understood [ 4 ]. In the current study, genome sequencing of persister-forming isolates revealed that they had smaller genomes (4.66–4.9 Mbp), compared to PAO1-genome (6.3 Mbp) sequenced previously [ 55 ], and the genome of Pseudomonas CF-isolates (6.36 Mbp) recently sequenced [ 50 ]. The smaller genome size for our isolates could be due to the short-reads-based sequencing and assembly used in our study.…”
Section: Discussionmentioning
confidence: 77%
“…Further investigation is required to explore the validity and features of this clade. Similarly, the phylogenetic analysis of P. aeruginosa CF isolates performed by Datar et al [ 50 ] revealed their unique clustering and indicate their location in different clades. To the best of our knowledge, our study is the first to study the genome sequence of persister isolates from local hospitals in Egypt.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Microbial and host factors furthermore impact the ongoing adaptive response exhibited by mutating strains within the airways of immunocompromised CF patients. This results in the acquisition of advantageous attributes such as virulence factor assembly, motility, antibiotic resistance, and metabolic adaptation [ 14 ]. Prior studies have shown that hypermutator strains may constitute up to 60% of all P .…”
Section: Introductionmentioning
confidence: 99%